Inclusive Prosperity: Bridging Finance and Community for SME Empowerment - Ramadhan, Yudi (Manunggal Halim Jaya, 2024)
This study investigates the synergistic impact of bridging finance and community support mechanisms on Small and Medium Enterprises (SMEs) empowerment and inclusive prosperity. Through a comprehensive literature review, the study aims to elucidate the multifaceted nature of bridging finance and community-based initiatives, highlighting their significance in fostering SME growth and resilience. The research employs a qualitative approach, drawing insights from existing theoretical frameworks and empirical studies to analyze the interplay between financial and non-financial factors in driving SME empowerment. Findings reveal that bridging finance initiatives, including working capital loans, trade finance facilities, and venture capital investments, play a pivotal role in addressing SMEs' short-term funding needs and enhancing their market competitiveness. Additionally, community support mechanisms, such as mentoring, networking, and capacity-building programs, contribute to SME empowerment by facilitating knowledge exchange, collaboration, and resource-sharing within local communities. The integration of bridging finance and community support offers a holistic approach to SME development, enabling stakeholders to create an enabling environment that supports SME growth, innovation, and socio-economic inclusion. The study underscores the importance of continued research and collaboration in advancing our understanding of the mechanisms driving inclusive prosperity and informing evidence-based policy and practice interventions aimed at promoting SME development and sustainable economic growth.